PP5 Factors related to completion and performance in a 150 km arctic ultramarathon. (21st October 2014) - Graham, GEA; Bamford, A; Thompson, M
Abstract : The term Ultramarathon is used to describe any foot race of a distance greater than 42.2 km. Races are run in a number of environments including Jungle, Desert and Arctic. The Rovaniemi 150 is a 150 km ultramarathon run inside the Arctic Circle. Previous studies have examined factors predictive of completion and performance in ultramarathons run in non-arctic conditions. There appears to be no research specific to ultramarathons undertaken in an arctic environment. This study aims to identify factors that are predictive of completion and performance in a 150 km Arctic ultramarathon. All runners in the 2014 Rovaniemi 150 Arctic Ultramarathon were asked to complete a questionnaire and have basic demographic data gathered. 26 runners started the race with a 73% response rate to the questionnaire (n = 19). Runners who successfully finished the race had a BMI 2.4 kg/m 2 less than non-finishers (p = 0.01) and a 2.1 cm greater mid-upper arm circumference (p = 0.05). Finishers also had faster marathon PBs and had completed more ultramarathons, but these findings only approached statistical significance (p = 0.06). In runners who finished the race better performance was positively correlated with quicker marathon PB (0.56), greater training volume (−0.47), greater training frequency (−0.49) and longest run in training for the race (−0.59). There was no relationship with BMI (0.05), but a larger arm mid-third circumference was correlated with better performance (−0.43). The authors think this is the first study examining factors related to completion and performance in an arctic ultramarathon. It largely confirms the findings of previous studies examining factors related to ultramarathon performance. The finding that larger mid arm circumference was associated with both finishing and performance differs from studies of non-arctic ultramarathons; this finding merits further investigation given the different biomechanics of running on snow.